Prevalence of Radiographic Knee Osteoarthritis After Anterior Cruciate Ligament Reconstruction, With or Without Meniscectomy: An Evidence-Based Practice Article - Ruano, Jennifer S. (J Athl Train, 2017)
REFERENCE: : Claes S, Hermie L, Verdonk R, Bellemans J, Verdonk P. Is osteoarthritis an inevitable consequence of anterior cruciate ligament reconstruction? A meta-analysis. Knee Surg Sports Traumatol Arthrosc. 2013;21(9):1967–1976. CLINICAL QUESTION: : What is the prevalence of radiographic knee osteoarthritis (OA) at a mean follow-up equal to or greater than 10 years after autologous anterior cruciate ligament (ACL) reconstruction, with or without meniscectomy? DATA SOURCES: : The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting guidelines were used to conduct this meta-analysis. Studies were identified by searching PubMed, MEDLINE, EMBASE, and Cochrane Library dating from their earliest file until October 2010. Key terms applied for searching were anterior cruciate ligament or ACL, autologous, follow-up, long-term, outcome, reconstruction, results, treatment, and (osteo)arthritis or osteoarthrosis. The reference lists of included studies were also manually checked to ensure that relevant articles were not omitted. STUDY SELECTION: : The authors limited their search to English- and French-language journals. Included studies provided radiographic outcomes after autologous ACL reconstruction and had a mean follow-up of ≥10 years. Excluded studies evaluated ACL reconstruction with major concomitant surgical procedures (eg, meniscal allograft transplantation, high tibial osteotomy). In addition, data from 2 studies completed by the same research team with identical patient populations were limited to the article with the longest follow-up. Finally, manuscripts with inaccurate or incomplete data were excluded. DATA EXTRACTION: : The following key characteristics of each study were extracted: type of study (prospective or retrospective); ACL surgical procedure (eg, open or arthroscopic bone-patellar tendon-bone graft); time frame of surgery; mean follow-up (in years) post–ACL reconstruction; total number of participants with radiographs; total number of participants with radiographic OA at follow-up; and number of participants with meniscectomy before, during, or after ACL reconstruction. Although the OA diagnosis was based on radiographic criteria, the included studies used 4 OA classifications and grading scales: Ahlbäck, Fairbanks, Kellgren and Lawrence, and International Knee Documentation Committee. Regardless of classification or grading scale, OA was defined as the presence of joint-space narrowing: Ahlbäck grades 1 through 5, modified Fairbanks grades 2 and 3, Kellgren and Lawrence ≥2, and International Knee Documentation Committee grades C and D. Tibiofemoral and patellofemoral OA data were collapsed due to the lack of reporting specificity among the studies. Participants were categorized into a meniscectomy or nonmeniscectomy group if this information was reported. Partial or total meniscectomies before, during, or after ACL reconstruction were collapsed regardless of location (medial or lateral compartment), and those patients who underwent a meniscal repair were grouped into the nonmeniscectomy group. Data were analyzed using odds ratios, the Cochran χ(2) test, and a random-effects meta-regression analysis. The DerSimonian and Laird approach was used to assess study heterogeneity. P values below .05 were considered statistically significant. MAIN RESULTS: : The initial computerized database search resulted in 211 possible studies. However, after the authors applied the inclusionary and exclusionary criteria, only 16 studies were relevant. A total of 1554 participants were available at the follow-up period. Mean follow-up ranged from 10 to 24.5 years; 11 of the 16 articles had a mean follow-up between 10 and 12 years. Heterogeneity was large (I(2) = 96%), which indicated that the included studies generated a wide range of knee OA prevalence (2%–79%). Almost 28% (95% confidence interval [CI] = 16.3%, 43.5%) of participants had radiographic knee OA. A total of 1264 participants were involved in studies that evaluated meniscectomies (n = 11). Among the 614 participants with either partial or total meniscectomies, 50.4% had radiographic knee OA (95% CI = 27.4%, 73.1%). In contrast, only 16.4% (95% CI = 7.0%, 33.9%) of those without a meniscectomy had radiographic knee OA. CONCLUSIONS: : The findings of Claes et al reflected a radiographic knee OA prevalence at a minimum average of 10 years' postautologous ACL reconstruction that was lower than commonly perceived (up to 79%). In addition, meniscectomy was an important risk factor (3.54-fold increase) for developing OA after ACL reconstruction.